Caracterização in vivo do destino das células-tronco da polpa dentária - Cucco, Carolina (2015)
Teeth exhibit limited repair in response to damage, and studies have shown that dental pulp stem cells (DPSCs) probably provide a source of cells to replace those damaged and to facilitate repair. Additionally, in vivo transplantation into immunocompromised mice demonstrated the ability of DPSCs to generate functional dental tissue in the form of dentine/pulp-like complexes. Therefore, the purpose of this study was to characterize the endothelial fate of DPSCs in vivo and to start to understand the role of Tie2/Ang-1 signaling pathway on the regulation of the endothelial differentiation of DSPCs.! DPSCs stably transduced with LacZ were seeded into tooth slices and implanted into immunodeficient mice for 7, 14, 21 ad 28 days. A combination of in vitro and in vivo assays were performed to determine the role of Ang-1 in the vasculogenic fate of DPSCs. Histologic analysis and immunohistochemistry from the retrieved tooth slices were performed. Dental pulp stem cells seeded in tooth slice/scaffolds and transplanted into SCID mice showed a continuous crescent number of beta-galactosidase-positive odontoblastic and endothelial cells along the 7, 14, 21 and 28 days of the study. At 21 days beta-galactosidase-positive capillaries located close to murine blood vessels were detected, confirming our previous report (Cordeiro et al, 2008; Sakai et al, 2010). DPSCs exposed to Ang-1 differentiated into cells expressing VEFGR2, CD31 and Tie2. Exposure of VEGFR1-silenced DSPC to Ang-1 and VEGF induced the activation of STAT3, Erk and Akt, while VEGF alone inhibited the phosphorylation of STAT3. This is consistent with the role of Akt and STAT3 in the regulation of cell survival and cell-cell interation of DPSC through Tie2/Ang-1 signaling pathway. This study demonstrates that Angiopoietin-1 is involved in the vasculogenic differentiation of DSPCs.